2021
DOI: 10.7554/elife.60360
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic memory requires CaMKII

Abstract: Long-term potentiation (LTP) is arguably the most compelling cellular model for learning and memory. While the mechanisms underlying the induction of LTP ('learning') are well understood, the maintenance of LTP ('memory') has remained contentious over the last 20 years. Here, we find that CaMKII contributes to synaptic transmission and is required LTP maintenance. Acute inhibition of CaMKII erases LTP and transient inhibition of CaMKII enhances subsequent LTP. These findings strongly support the role of CaMKII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 98 publications
3
51
0
1
Order By: Relevance
“…The importance of CaMKII activity, and its idiosyncratic subunit arrangement in dodecameric holoenzymes, have stimulated great interest in its mechanisms of action. Particularly beguiling is the idea that CaMKII can convert brief Ca 2+ signals corresponding to decisions, calculations and comparisons in neurons into sustained phosphorylation of targets in order to store information in neural circuits (Lisman, Schulman and Cline, 2002; Coultrap and Bayer, 2012; Tao et al ., 2021). The prevailing model for the requisite spatial and temporal spread of CaMKII autonomous activity argues that CaMKII must exchange subunits between activated and naïve (unactivated) holoenzymes (Stratton et al ., 2014; Bhattacharyya et al ., 2016), principally because previous work suggests autophosphorylation between holoenzymes does not occur (Miller, S. G. & Kennedy, 1986; Hanson et al ., 1994; Rich and Schulman, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CaMKII activity, and its idiosyncratic subunit arrangement in dodecameric holoenzymes, have stimulated great interest in its mechanisms of action. Particularly beguiling is the idea that CaMKII can convert brief Ca 2+ signals corresponding to decisions, calculations and comparisons in neurons into sustained phosphorylation of targets in order to store information in neural circuits (Lisman, Schulman and Cline, 2002; Coultrap and Bayer, 2012; Tao et al ., 2021). The prevailing model for the requisite spatial and temporal spread of CaMKII autonomous activity argues that CaMKII must exchange subunits between activated and naïve (unactivated) holoenzymes (Stratton et al ., 2014; Bhattacharyya et al ., 2016), principally because previous work suggests autophosphorylation between holoenzymes does not occur (Miller, S. G. & Kennedy, 1986; Hanson et al ., 1994; Rich and Schulman, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CaMKII is a key protein kinase involved in neural plasticity and memory formation [ 79 , 80 , 81 , 82 ]. Experimental blocking of CaMKII inhibits synaptic transmission [ 83 ]. Accordingly, in our studies, we observed a decrease in the expression level of the CaMKII gene predominantly in the strains with double deletions and strains with CBS deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Over three decades of study suggests that CaMKII is one of the key players in LTP ( Zalcman et al, 2018 ). Inhibition of CaMKII activity blocks the induction as well as maintenance of LTP ( Malenka et al, 1989 ; Malinow et al, 1989 ; Tao et al, 2021 ). In response to sufficient influx of Ca 2+ into the postsynaptic neuron, CaMKII gets activated by the binding of Ca 2+ /CaM and autophosphorylated at Thr 286 .…”
Section: Ca 2+ /Calmodulin-dependent Protein Kinas...mentioning
confidence: 99%
“…While considerable insights have been obtained on the mechanisms by which LTP-inducing tetanic stimuli are converted to enhanced AMPAR activity at the postsynaptic side, the mechanisms by which the potentiated state is maintained has been intensively debated ( Giese et al, 1998 ; Buard et al, 2010 ; Coultrap et al, 2012 ; Chang et al, 2017 ; Giese, 2021 ; Tao et al, 2021 ). Even long-lasting structural changes such as spine enlargement are maintained by dynamic molecular mechanisms ( Gamache et al, 2020 ).…”
Section: Ca 2+ /Calmodulin-dependent Protein Kinas...mentioning
confidence: 99%
See 1 more Smart Citation